Immunobiotic bifidobacteria strains modulate rotavirus immune response in porcine intestinal epitheliocytes via pattern recognition receptor signaling - Ishizuka, Takamasa (2016)
In this work, we aimed to characterize the antiviral response of an originally established porcine intestinal epithelial cell line (PIE cells) by evaluating the molecular innate immune response to rotavirus (RVs). In addition, we aimed to select immunomodulatory bacteria with antiviral capabilities. PIE cells were inoculated with RVs isolated from different host species and the infective titers and the molecular innate immune response were evaluated. In addition, the protection against RVs infection and the modulation of immune response by different lactic acid bacteria (LAB) strains was studied. The RVs strains OSU (porcine) and UK (bovine) effectively infected PIE cells. Our results also showed that RVs infection in PIE cells triggered TLR3-, RIG-I- and MDA-5-mediated immune responses with activation of IRF3 and NF-κB, induction of IFN-β and up-regulation of the interferon stimulated genes MxA and RNase L. Among the LAB strains tested, Bifidobacterium infantis MCC12 and B. breve MCC1274 significantly reduced RVs titers in infected PIE cells. The beneficial effects of both bifidobacteria were associated with reduction of A20 expression, and improvements of IRF-3 activation, IFN-β production, and MxA and RNase L expressions. These results indicate the value of PIE cells for studying RVs molecular innate immune response in pigs and for the selection of beneficial bacteria with antiviral capabilities.